2015
DOI: 10.1007/s00604-015-1489-5
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide nanoparticle-enhanced ultrasensitive chemiluminescence immunoassay for the carcinoma embryonic antigen

Abstract: An ultrasensitive enzyme-linked immunosorbent assay (ELISA) is reported for the determination of carcinoma embryonic antigen (CEA) in human serum. It was realized using a microplate reader using a 384-well plate. Monoclonal antibody (Ab) against CEA (1°Ab) acting as the capture probe was immobilized on zinc oxide nanoparticles (ZnONPs) in the form of self-assembled monolayers (SAMs). CEA captured by 1°Ab was quantified using a sandwich ELISA wherein a polyclonal second antibody against CEA (2°Ab) was used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…They discovered that ZnO-NPs could significantly be used in the systems of cancer diagnosis. Additionally, Pal and Bhand [138] developed the ZnO-NP-based test of ELISA for detecting serum levels of cancer antigens of embryonic. The detection system consisted of a monoclonal carcinoma embryonic antigen-antibody conjugated to ZnO-NP, which formed self-assembled monolayers, and even at 1 pg/ml, smaller quantities of antigen were found [139].…”
Section: Biosensormentioning
confidence: 99%
“…They discovered that ZnO-NPs could significantly be used in the systems of cancer diagnosis. Additionally, Pal and Bhand [138] developed the ZnO-NP-based test of ELISA for detecting serum levels of cancer antigens of embryonic. The detection system consisted of a monoclonal carcinoma embryonic antigen-antibody conjugated to ZnO-NP, which formed self-assembled monolayers, and even at 1 pg/ml, smaller quantities of antigen were found [139].…”
Section: Biosensormentioning
confidence: 99%
“…This research showed that NaTPB and PPP on CL had a synergistic effect. Pal and Bhand (2015) In the study of bromophenol red and bovine serum albumin (BSA) as the luminol signal co-enhancers in chemiluminescent detection of sequence-specific DNA, the CL signal was increased up to 6×10 4 when bromophenol red and BSA were placed into the luminol-H 2 O 2 -HRP system as the co-enhancers. The results indicated that BSA in the bromophenol red-enhanced CL system showed 36 times stronger CL signals than that without BSA addition.…”
Section: Applications Of Secondary Enhancersmentioning
confidence: 99%
“…Zinc stabilized the luminol radical, increasing the half-life of this radical in the medium). Pal and Bhand (2015) utilized zinc oxide nanoparticle to enhance CL signals of luminol and LOD for the determination of carcinoma embryonic antigen (CEA) in human serum. The CL signal of luminol tripled over the conventional ELISA and the limit of quantitation became as low as 1 pg mL −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, with the development of analytical techniques, many methods for CEA detection in real samples have been reported. These methods include fluorescence immunoassay, 6 electrochemical analysis, 7 chemiluminescence immunoassay, 8 and surface plasmon resonance. 9 However, convenient and low-cost methods are still required in clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%